12 UMP academicians among worlds top scientists - T.N., Alagesh (The New Straits Times Press (M) Bhd., 2021)
PEKAN: 12 Universiti Malaysia Pahang (UMP) lecturers have been listed as among the world's "Top 2% Scientist" in various fields and disciplines by Stanford University.